Initial treatment of a patient with ventricular tachycardia: Case report - Krstić Teodora; Radulović Milovan; Marić Nikolina; Đuričin Aleksandar; Jokšić-Zelić Milena; Vasović Velibor; Petrić Aleksandra; Latinović Simeon; Jokšić-Mazinjanin Radojka (ABC: časopis urgentne medicine)
Ventricular Tachycardia (VT) is defined as any rhythm with more than 120 beats per minute originating distally from the His bundle, in the ventricular myocardium, outside the actual conduction system, and represents a life-threatening arrhythmia. The treatment of VT is based on certain principles that depend on the hemodynamic stability of the patient. If the patient is hemodynamically unstable, electrical cardioversion should be initiated, and if the patient is hemodynamically stable, pharmacological therapy is applied. Case Report: An 80-year-old woman complains of shortness of breath and loss of consciousness. The patient is lying down, responds to verbal stimuli, with unmeasurable blood pressure and oxygen saturation in peripheral blood. Upon sitting up, she loses consciousness. The electrocardiogram (ECG) shows monomorphic ventricular tachycardia, with a frequency of approximately 230 beats per minute. Analgesosedation with midazolam and tramadol was administered, followed by three DC shocks. Sinus rhythm was established at a frequency of 110/min., and after the administration of 300 mg of amiodarone, the heart rate was 85/min., blood pressure was 75/45 mmHg, and SpO2 was 96%. The patient was admitted hemodynamically stable to the Coronary Care Unit of the Cardiology Department. Conclusion: Ventricular tachycardia (VT) is a serious emergency condition frequently encountered by emergency medical teams, and its recognition and prompt action are crucial for a successful outcome. Due to the wide range of clinical manifestations VT can cause, recognizing it as an urgent condition can be challenging, making the diagnosis sometimes difficult. Therefore, continuous education of emergency medical teams, adopting new guidelines, and updating existing protocols are of paramount importance to improve the quality of healthcare provided.